Hand gesture for nano-quadcopter control - Huang, Zhibin (2015)
Over the years, quadcopter have been increasingly been used by university researches to test and evaluate new ideas such as flight control theory and real time system, the numerous advantages to using quadcopters such as cost, variety in sizes and simple mechanical design makes it ideal for amateurs to handle when, eventually Nano Quadcopters were introduced when minimizing the quadcopters, sparking a whole new interest at its undiscovered potential. Some of the minor challenges in regards to Nano quadcopter are its ability to stabilize and “Hover” in mid-air, hence the project aims to control the nano quadcopters using simple hand-gesture. With the increased applications of Microsoft kinect, this projects aims to apply Kinect as its controller to manoeuvre the Nano quadcopter and explore its possibilities.